Near-chromosome level genome assembly of devil firefish, Pterois miles - Kitsoulis, Christos V.; Papadogiannis, Vasileios; Kristoffersen, Jon B.; Kaitetzidou, Elisavet; Sterioti, Aspasia; Tsigenopoulos, Costas S.; Manousaki, Tereza (Peer Community Journal)

(untitled)
Devil firefish (Pterois miles), a member of Scorpaenidae family, is one of the most successful marine non-native species, dominating around the world, that was rapidly spread into the Mediterranean Sea, through the Suez Canal, originating from the Indian Ocean. Even though lionfishes (Scorpaenidae) are identified among the most prosperous marine invaders, within this taxonomic group, the genomic resources are scant, while reference genome assemblies are totally absent. Here, we built and analyzed the first reference genome assembly of P. miles and explored its evolutionary background. The resulting genome assembly consisted of 660 contigs and scaffolds (N50 = 14,5 Mb) with a total size of about 902 Mb, while delivering 98% BUSCO completeness. We identified and described the large amount of transposable elements present in the genome and based on genomic data we constructed the first teleost phylogeny which includes a member of genus Pterois. The high-quality and contiguity de novo genome assembly built herein provides a valuable resource for future studies in species’ biology and ecology, lionfish phylogeny, the influence of transposable elements on the evolution of vertebrate genomes and fish toxins evolution.